Ketidakseragaman Sebaran Spasial Variabilitas Musiman Eddy di Perairan Barat Laut Indonesia - Aditya Rakhmat Kartadikaria; Gandhi Napitupulu; Kalaka Rangga; Ivonne Milichristi Radjawane; Faizal Ade Rahmahuddin Abdullah (Jurnal Kelautan Tropis, 2024)
Sea level anomaly (SLA) data spanning from 1993 – 2022 were used to analyze the characteristic of eddy current in Northwest Indonesian. An improved winding angle method was used and was able to detect 1663 anticyclonic eddies (AEs) and 1748 cyclonic eddies (CEs). The average eddy lifespan is approximately four weeks. The eddy in the West Indonesian Ocean has a radius ranging from 40 – 100 km and a high number of mesoscale eddy (radius more than 100 km) detected in the northern area of West Indonesian Ocean (4° N - 10° N). The eddy kinetic energy (EKE) increased proportionally with their radius, whereas the eddy vorticity decreased proportionally with their increasing radius. The seasonal cycles of eddy circulation in the west Indonesian Ocean were differ for both AEs and CEs, where AEs were dominated during east monsoon season (JJA) and CEs came with longer periods from November to March, yet for both AEs and CEs they have similar radius per month. During weak periods of both eddies, their meridional distributions differ; CEs tend to be formed in relatively lower latitude, while AEs were concentrated in relatively higher latitude.